Endometriosis and infertility: Updates on the pathophysiological aspects and treatment of the association (Research, Society and Development, 2024)
Introduction: Endometriosis is a benign gynecological disorder that mainly affects women of childbearing age. As a multisystem disease, in addition to the female reproductive system, intestinal portions and structures of the urinary system can also be affected. Its pathophysiology is complex and multifactorial, as is establishing the diagnosis. Treatment is multidisciplinary and multimodal. Objective: The aim of this study was to evaluate the clinical, epidemiological and pathophysiological aspects of the association between infertility and endometriosis. Materials and Methods: This is an integrative literature review on the general clinical characteristics of the association between endometriosis and infertility. The PICO strategy was used to develop the guiding question. In addition, the descriptors "Endometriosis"; "Infertility"; "Treatment" were cross-referenced in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar and Virtual Health Library (VHL) databases. Results and Discussion: The studies show that the association between endometriosis and infertility involves specific nuances within medicine, including pathophysiological, clinical, epidemiological and therapeutic aspects. Conclusion: The association between infertility and endometriosis is already well established in the literature and involves the interaction of multiple pathophysiological factors. In order to deal with it correctly, there are now drug and surgical techniques as well as assisted reproduction techniques, and the doctor must analyze and select the most appropriate treatment for each patient.